Highly selective synthesis of mono-ethylene glycol phenyl ethers via hydroxyalkoxylation of phenols by cyclic carbonates using large pore zeolites - Kinage, Anil K.; Gupte, Sunil P.; Chaturvedi, Rajiv K.; Chaudhari, Raghunath V. (Catalysis Communications, 2008)
Hydroxyalkoxylation of phenols by cyclic carbonates catalyzed by alkali loaded large pore zeolites has been reported. The study shows that KL type zeolite was recyclable and selective in producing mono-ethylene glycol pheryl ethers in similar to 98.5% yield. Various substituted simple phenols were converted into mono-ethylene glycol ether of phenols with over 90% yields, except 3-bromo and 2-methyl phenols. Mono hydroxyl plienols such as hydroquinone, biphenol and BPA (2,2-bis(4-hydroxyphenyl)propane) also produce corresponding mono- and di-ethylene glycol ethers. The ratio of ethylene carbonate to phenol was found to be critical for selective formation of monoethylene glycol phenyl ether of phenols. A ratio of two results in formation of appreciable amount of diether derivative viz., 2-(2-phenoxyethoxy) ethanol. Compared to ethylene carbonate, a lower reactivity of 1,2-propane carbonate was found for hydroxyalkoxylation of phenol. It was found that ring opening at less hindered methylene carbon of 1,2-propylene carbonate prevailed giving rise to selective formation of beta-hydroxy phenyl ethers. The reactivity of ethylene carbonate towards O-alkylation versus transesterification of phenol has been explained on the basis of HSAB concept. Finally, it has been shown that yield of mono-ethylene glycol phenyl ether is controlled both by basicity and channel architecture of zeolite structure. KL zeolite was found to be the most effective zeolite because of it's intermediate basicity and one dimensional channel architect. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cyclic carbonate; ethylene glycol phenyl ether; hydroxyalkoxylation; phenol

Growth of hydrothermally stable meso-porous silica structure interconnected around micro-porous zeolite crystals - Kinage, Anil K.; Prashar, Atul K.; Berlier, Gloria; Chaturvedi, Rajiv K. (Materials Characterization, 2011)
The growth of hydrothermally stable ordered meso-porous silica with M41S type structure interconnected around zeolite crystals was achieved from seeds normally nucleating the crystallization of micro-porous zeolite. The solid state NMR and FT-IR showed species like Si(OSi)(3)OH and Si(OSi)(2)(OH)(2) (or Q(3) and Q(2) sites, respectively) are formed during first hydrothermal treatment with surfactant and NaOH. These species and surface silanol group of zeolite crystal condense to give meso-porous silica structure interconnected around zeolite crystal during re-crystallization at lower pH. Resulting meso-micro-porous hybrid material is found to be highly active, selective and stable in the synthesis of 2-(phenylamino) ethanol from aniline and ethylene carbonate compare to parent ZSM-5 and pure MCM-41. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrothermal stability; Interconnected meso-porous silica; Meso-micro hybrid material; Synthesis of amino alcohol